The Legitimacy of Citizenship Education. Philosophical Issues - Ostinelli, Marcello (Swiss Journal of Educational Research, 2020)
Recently the educational task of the public school has been repeatedly challenged. Citizenship has not been spared from criticism and its legitimacy has been questioned. The article discusses the issue of the legitimacy of citizenship education in public schools, specifying the meaning of neutrality of which it proposes a narrow interpretation.On this basis the article examines four philosophical models of citizenship education (communitarianism, civic humanism, liberalism, republicanism). The analysis suggests that the republican model of citizenship education is the most appropriate; it needs however a liberal adaptation. The proposed solution of a liberal republicanism is illustrated with a critical examination of the duty of civility.